Analisis Response Time Penatalaksanaan Rujukan Kegawatdaruratan Obstetri Ibu Hamil - Tirtaningrum, Dwi Ayu; Sriatmi, Ayun; Suryoputro, Antono (Media Kesehatan Masyarakat Indonesia, 2018)
Semarang government established PONED Health Center and PONEK Hospital for referral in managing obstetric cases. In fact, response time referral is still long to get the service by patients. Research purposes, analyze of response time in the management obstetric maternal emergency referral in Semarang. Type of survey research with qualitative descriptive approach and purposive technique. Data collection using indepth interviews, documentation, and source triangulation.The results, response time implementation and acceptance of referral has not been optimal as patient expectation. Length of time the patient came to the emergency room of Health Center until ready referred to the PONEK Hospital 1-2 hours. Length of time the patient receives at the emergency room of PONEK Hospital until get treatment room 2 -3 hours. The problem because responsiveness of the medical team responding to patients, maternal not carrying MCH books and not completing administrative, ambulance driver difficult to contact, confirmation of information from referral hospital and duration of patients transfer process from delivery room to treatment room.